Interactive real-time games portal (b) - Phyo, Wai Lin. (2010)
The Interactive Real-time games have become increasingly popular as high speed Internet connections have helped developed the online massively-multiplayer gaming world. The Real-time games provides all that graphical activity at high frame-rates while responding quickly to user inputs are the main challenges when programming such kinds of games. For interactive games the communication with other programs is also an important factor. The programming languages have to meet these requirements to provide a useful framework for the development of interactive real-time games. The purpose of this report is to address the key issues and challenges in developing such an Interactive Real-time Games Portal. The development process, how the developed system communicate on client-server architecture with the server controlling and mediating the game state as well as directing messages will be discussed and illustrated. A detail explanation on how to make use of web technology to monitor Real-time Games will also be discussed.